The World Bank Annual Report 2018 - World Bank (Washington, DC: World Bank, 2018)
The Annual Report is prepared by the Executive Directors of the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA)--collectively known as the World Bank--in accordance with the by-laws of the two institutions. The President of the IBRD and IDA and the Chairman of the Board of Executive Directors submits the Report, together with the accompanying administrative budgets and audited financial statements, to the Board of Governors.